Married and still loving it : the joys and challenges of the second half - Chapman, Gary D., 1938-; Myra, Harold (Moody Publishers, 2016)
In Married and Still Loving It, renowned relationship expert Gary Chapman and Harold Myra, longtime CEO of Christianity Today International, offer wise counsel and practical insight on making your marriage thrive during these years. Real couples share honestly about their joys and struggles, including Jerry and Dianna Jenkins and Ken and Joni Eareckson Tada, who talk movingly about their marital journeys. Married and Still Loving It feels like a gathering of kindred spirits. It will inspire and equip you to embrace the adventures yet ahead, hand in hand with the one you love.